Understanding Rabies Disease With The Making Of Eco-Enzyme Soap For Hand Washing - Lubis, Irfan Darfika; Salsabila, Saumunnisa; Aulia, Silvi; Salam, Ghurvah; Edysti, Edysti; Arhimza, Afwan (Buletin Farmatera, 2026)
Abstract: Rabies is a zoonotic disease caused by the rabies virus with a mortality rate of nearly 100% if not treated properly. The lack of public understanding about the dangers of rabies and the lack of awareness about the importance of hand hygiene as a preventive measure against infectious diseases such as rabies are health issues that need to be addressed through this education program. This activity was carried out as part of community service on August 21-22, 2025, at SMPN 3 Kutalimbaru Satu Atap, Namo Rube Julu Village, Deli Serdang Regency, North Sumatra Province, involving male and female students. The implementation method consisted of interactive counseling on rabies using educational posters, followed by an open discussion session and an evaluative quiz, and concluded with a workshop on making eco-enzyme soap using environmentally friendly materials. The results of the activity showed an increase in students' understanding of the transmission mechanism of rabies, the characteristics of symptoms in animals and humans, initial steps to take when exposed to the virus, and practical skills in producing eco-enzyme soap as a sustainable cleaning product alternative and as a preventive measure against rabies. Participants showed high enthusiasm and responded positively to the material presented, as well as successfully raising awareness about the importance of maintaining hand hygiene. Thus, the rabies education program combined with eco-enzyme soap making training proved effective in improving students' knowledge and practical skills, so that it is hoped that this will become a healthy habit that is consistently applied in daily activities.